(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2024)
In this research, an exploration of advances in the evaluation of microorganisms as biocontrol agents of pathogens that cause diseases in rice cultivation was carried out; For this purpose, scientific articles published in journals indexed in databases such as Scopus, Scielo, Redalyc, Springer, among others, were reviewed and research was analyzed in which antagonistic agents of pathogens in rice have been used. This review article addresses the need to implement control strategies that minimize environmental impact and promote sustainability and aims to analyze current advances in the evaluation of microorganisms as biocontrol agents of disease-causing pathogens in rice cultivation. Among the main findings, it is mentioned that there are various microorganisms (fungi and bacteria) such as Trichoderma spp., Bacillus subtilis, Lysobacter antibioticus, Bacillus cereus, Bacillus spp., among others, that have demonstrated the ability to suppress pathogens that cause rice diseases, due to mechanisms of action such as antibiosis, competition for nutrients, mycoparasitism, induction of systemic resistance in plants. This multiplicity of mechanisms allows the microorganism to be selected as a biological control agent. Likewise, there is a trend to apply integrated approaches to take advantage of microbial diversity, improving plant health and reducing dependence on agrochemicals.